SOLE Prize for Contributions to Data and Measurement (Journal of Labor Economics, 2021)
Previous articleNext article FreeSOLE Prize for Contributions to Data and MeasurementFull TextPDF Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJohn C. Haltiwanger is the 2021 recipient of the SOLE Prize for Contributions to Data and Measurement. John is Distinguished University Professor of Economics at the University of Maryland. He is a fellow of the Society of Labor Economists and a fellow of the Econometric Society as well as the recipient of the 2013 Julius Shiskin Award for Economic Statistics, the 2014 Roger Herriot Award for Innovation in Federal Statistics, and the 2020 Global Entrepreneurship Research Award.John has made path-breaking contributions to the development of new measures of economic activity. Even if aggregate employment is relatively stable, significant restructuring typically is occurring in the form of job creation at some firms simultaneously with job destruction at others. Working with administrative data housed at the US Census Bureau, John and his early collaborators pioneered the development of measures of job creation and job destruction that capture this sort of dynamic restructuring. These measures are now an important foundation for a large volume of research and policy analysis in this area.Building on this work, John has produced invaluable evidence concerning the contributions of small businesses versus new businesses to economic growth. In another stream of research, he has demonstrated the importance of the entry and growth of firms with above-average productivity and the decline and exit of firms with below-average productivity to aggregate productivity growth. An important pattern documented in John’s work is the decline in economic dynamism in recent decades, a finding with significant implications for economic opportunity and growth.More recently, John has turned his attention to the use of private sector “big data” to improve and supplement official economic statistics. Approaches to using these data such as those he and his collaborators are developing will be critical to capturing patterns of economic activity in the future, particularly as traditional methods face challenges and the structure of the US economy evolves.John’s contributions to the improvement of economic measurement go far beyond his own research. He was central to the development of the Census Bureau’s Longitudinal Business Database (LDB) and Business Dynamics Statistics (BDS) programs. He also made important contributions to the development of the Longitudinal Employer-Household Dynamics (LEHD) program and, more recently, the new Business Formation Statistics (BFS). These data products have proven to be of enormous value to the research community. In addition, John has mentored and collaborated with dozens of students and younger scholars, many of whom have gone on to do their own important work related to the measurement of economic activity.Awarding John Haltiwanger the 2021 SOLE Prize for Contributions to Data and Measurement is a fitting recognition of his many contributions to improving the nation’s economic statistics.2021 SOLE Prize Nominating Committee:Katharine Abraham (chair)Nick BloomKaren DynanErika McEntarferRobert Moffitt (ex officio)John SabelhausDavid Weir Previous articleNext article DetailsFiguresReferencesCited by Journal of Labor Economics Volume 39, Number 3July 2021 Published for the Society of Labor Economists, Economics Research Center/ NORC Article DOIhttps://doi.org/10.1086/715498 Views: 568 © 2021 by The University of Chicago. All rights reserved. Crossref reports no articles citing this article.